In utero drug exposure and hearing impairment in 2-year-old children A case-control study using the EFEMERIS database. (October 2018) - Foch, Caroline; Araujo, Mélanie; Weckel, Alexandra; Damase-Michel, Christine; Montastruc, Jean-Louis; Benevent, Justine; Durrieu, Geneviève; Lacroix, Isabelle
Abstract: Introduction: As the ear development extends from the 4th to the 30th week of pregnancy, in utero exposure to ototoxic drugs might lead to hearing impairment in the fetus. The main study objective was to assess the association between in utero drug exposure and the occurrence of hearing impairment in 2-year-old children. Methods and materials: A case-control study was carried out using the EFEMERIS database, recording medications dispensed during pregnancy and the compulsory health certificates for child at 8 days, 9 and 24 months. Cases were defined as children with an abnormal hearing examination recorded on the 24-month certificate and controls as children with a normal hearing examination. Exposure was defined as at least one prescription and dispensation to the mother of drugs grouped at the 3rd level of the Anatomical Therapeutic and Chemical Classification level, compared to no exposure. Univariate logistic regressions were carried out. If the 95% confidence interval (95% CI) of the odds ratio (OR) was significant, a multivariable logistic regression was performed, adjusted on confounders. Results: A total of 1, 245 cases with abnormal hearing evaluation and 28, 046 controls were selected for analysis. Case and control mothers were comparable in terms of age, education and congenital infection. Cases and controls were comparable in terms of prematurity, asphyxia and weight at birth. However, among cases (versus controls), there were more ear deformities (0.6% vs 0.0% p≤0.001), and more recurring otitis (11.3% vs 5.3% p≤0.0001). When adjusted on confounders, the following drugs remained significant versus no exposure: acetylsalicylic acid at low dosage (OR 95% CI 1.61 [1.09-2.37]), valproic acid or valpromide (OR 95% CI 5.20 [1.93-14.00]), systemic corticosteroids (OR 95% CI 0.75 [0.61-0.93]. In a sensitivity analysis which excluded children with recurrent otitis at 24 months, these three results remained significant. Conclusions: This is the first study evaluating the risk of hearing disorders due to in utero exposure to drugs. Hearing loss was associated with valproic acid and low-dose acetylsalicylic acid exposure during pregnancy. Conversely, children with normal hearing were more likely to have been exposed in utero to corticosteroids than children with hearing loss.